Nanoporous palladium anode for direct ethanol solid oxide fuel cells with nanoscale proton-conducting ceramic electrolyte - Li, Yong (2017)
In this work, we demonstrate the operation of micro-solid oxide fuel cells (μ-SOFCs) with nanoscale proton-conducting Y-BaZrO3 (BZY) electrolyte to avoid the fuel crossover problem for direct ethanol fuel cells (DEFCs). The μ-SOFCs are operated with the direct utilisation of ethanol vapour as a fuel and Pd as anode at the temperature range of 300–400 °C. The nanoporous Pd anode is achieved by DC sputtering at high Ar pressure of 80 mTorr. The Pd-anode/BYZ-electrolyte/Pt-cathode cell show peak power densities of 72.4 mW/cm2 using hydrogen and 15.3 mW/cm2 using ethanol at 400 °C. No obvious carbon deposition is seen from XPS analysis after fuel cell test with ethanol fuel.